2022
DOI: 10.1186/s12905-022-01860-5
|View full text |Cite
|
Sign up to set email alerts
|

Current situation of menstruation and gynecological diseases prevalence among Chinese women: a cross-sectional study

Abstract: Background Gynecological diseases have been taken attention and studied worldwide. Although, no recent studies have delineated the magnitude of gynecological diseases among Chinese women. This study aims to evaluate the current situation of menstruation and gynecological diseases prevalence among Chinese women. Methods A cross-sectional study was conducted at a hospital affiliated with Nanjing medical university in Nanjing, China between September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In addition, Braet et al [14] used the Dutch Eating Behavior Scale, and Stunkard et al [15] used the three-factor eating behavior scale as a measuring tool to confirm that the food response dimension had a strong positive correlation with BMI. The above research indicates that the higher the response of children to food, the higher the risk of obesity, and obesity is one of the important risk factors for precocious puberty [16]. Therefore, we believe that more food orientation behavior is an important risk factor for breast development and gonadal axis activation in girls.…”
Section: Table 3 Dietary Preference and Intake Of The Three Groups Of...mentioning
confidence: 87%
“…In addition, Braet et al [14] used the Dutch Eating Behavior Scale, and Stunkard et al [15] used the three-factor eating behavior scale as a measuring tool to confirm that the food response dimension had a strong positive correlation with BMI. The above research indicates that the higher the response of children to food, the higher the risk of obesity, and obesity is one of the important risk factors for precocious puberty [16]. Therefore, we believe that more food orientation behavior is an important risk factor for breast development and gonadal axis activation in girls.…”
Section: Table 3 Dietary Preference and Intake Of The Three Groups Of...mentioning
confidence: 87%
“…Nonetheless, the study reported declining age-standardized incidence rates (ASIR) by nearly 30% in 2019 and that the overall ASIR was −1.2% (95% CI: −1.20, −1.10). A recent study from China that recruited patients between September 2021 and February 2022 reported that endometriosis remains to be one of the most prevalent gynecological diseases [ 47 ]. This study found a slightly lower prevalence of endometriosis (4.09%) than studies from other countries.…”
Section: How Common Is Endometriosis?mentioning
confidence: 99%
“…Uterine adenomyosis is a significant gynecological condition characterized by the invasive growth of endometrial tissues into the uterine muscle, resembling malignant tumors in its implantation and recurrence patterns ( 1 , 2 ). This condition impacts women’s health, frequently manifesting through symptoms like dysmenorrhea, chronic pelvic pain, and infertility ( 3 ). In China, the prevalence of adenomyosis among women varies widely, reported between 5% and 70%.…”
Section: Introductionmentioning
confidence: 99%